Puppet staging through media creation workshop as the development of character building model for the marginal in Bengawan Solo Riverbanks / Endang Widiyastuti - Widiyastuti, Endang (2016)
The crucial problem of today’s society is a state of psychological and moral personality of the individual. Moral issues could not be separated from the reality in society. The reports in social media today gives a rough idea of the form of society, especially in the city of Solo. Character building is still become a polemic. For parties outside of education, the importance of character building is less perceived. Solution could be done by dedication through training in the Puppet Creation Workshop for children in Bengawan Solo river banks. Training activities phase consist of, 1) Preparation and provisioning; 2) Implementation of dedication in the form of puppet creation workshop activity that consist of several stages, including: gathering and identifying, imagination, creation, processing, make a story, and staging; 3) The puppet staging made by children along the riverbank of Bengawan Solo. Results of dedication provide new experiences to children in Bengawan Solo river banks with a mission to introduce the cultural traditions that were mixed with modern culture, so that children appreciate life and culture. Second, the child’s skill competency to proceed visual sketching, cutting, pasting, coloring, assembly, finishing dongdang puppet (made from banana’s midrib attached to cardboard) can be explored and developed as well as the ability to play the puppet creations. Lastly, the child’s ability of thinking process to make the story from prologue to epilogue. Continuously long-term dedication implemented can realize achievement the value increases and manners implementation that children owned in Bengawan Solo river banks.